Progressive Income Taxation and Inflation: The Macroeconomic Effects of Bracket Creep - Lukas Hack (ZBW - Leibniz Information Centre for Economics, 2024)
Under nominal progressive taxation, inflation drives up tax rates if the schedule is not adjusted, leading to bracket creep. To isolate bracket creep from other sources of tax rate changes, I propose a non-parametric decomposition of changes in tax rates. Applying the decomposition to German administrative tax records, I find sizeable bracket creep episodes. While the overall importance of bracket creep has decreased over time due to institutional changes, the post-Covid inflation surge led to a resurgence. I characterize how bracket creep affects labor supply decisions in a partial equilibrium framework. Further, I estimate a theory-consistent measure of bracket creep, the indexation gap, which is used to discipline a New Keynesian model with incomplete markets. The model predicts that a given reduction in inflation via a monetary contraction leads to less output costs in an economy with bracket creep.
Keywords: E31; E62; H24; 330